On the Minimum Distance of One-Point Castle AG Codes (2012)
We present a characterization of the lower bound d* for minimum distance of algebraic geometry one-point codes coming from castle curves. This article shows explicit calculations of this bound in the case of a Weierstrass semigroup generated by two consecutive elements. In particular, we obtain a simple characterization of the exact value of the minimum distance Hermitian codes.